ENHANCING ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH PRINCIPAL-DRIVEN ENGINEERING STRATEGIES - zahro, fatimatus (Universitas Nurul Jadid, 2022)
This study is grounded in the recognition that numerous school principals seek assistance in optimizing the potential of their human resources within their educational institutions. As a consequence, the attainment of desired objectives becomes a formidable endeavor. The primary objective of this investigation is to identify and elucidate the methodologies employed by a junior high school principal in the Probolinggo district to enhance organizational citizenship behavior. Employing a qualitative phenomenological approach, the researcher conducted interviews, observations, and documentation to acquire credible and reliable data. The analysis of data adheres to the analytical framework proposed by Milles and Hubberman, encompassing data collection, data reduction, data presentation, and drawing conclusions. The findings of this inquiry illuminate five pivotal focal points within the principal's strategic approach to bolster organizational citizenship behavior through their leadership role: firstly, strategic planning; secondly, task allocation and organization; thirdly, motivation; fourthly, oversight and control; and fifthly, evaluation. This study underscores the implications of organizational citizenship behavior in facilitating the effective attainment of organizational objectives.